Assessment of Atmospheric Pollution from Particulate Matter and Heavy Metals in Urban Environment of Tirana (Albania) - Totoni (Lilo), R.; Cullaj, A. (Asian Journal of Chemistry, 2010)
The content of PM10 (particles smaller than about 10 μm in diameter) in the air and the concentration of seven heavy metals in the aerosol samples collected in three sites in Tirana city during the two year period (1997-1998) are presented. High particulate matter values, that exceeded in 82% of cases the WHO-AQG limit for TSP (100 μg/m3) are found. Heavy metal concentrations in particulate matter (PM), especially lead and cadmium, are much lower compared to the respective levels in Europe and USA urban areas. A discussion of possible sources of particulate matter and heavy metals content is presented,· based on obtained data and their statistical analysis using multi-variate techniques.